A Project Report on Distributed Network Crypto Server - ROHITH, SHIVASHANKAR, SRINATH and UDAY KUMAR (2007)
INTERNAL GUIDE: LATHA B, MVJCE EXTERNAL GUIDE: RAJESH, PROJECT LEADER, EFFENT TECHNOLOGIES
Keywords: Distributed Network Crypto Server